The Using of the Comic Application as Learning Medium for Islamic Study in Elementary School - Khoiriyati, Wildatun Rizka; Harahap, Hasda Nami; Sinaga, Rizky Awaliyah (Khalifa Journal of Islamic Education, 2021)
The study aimed to analyze how students evaluate the comic application as a learning medium, how to design a comic application product as a literacy medium for students in studying Islamic teachings. The study was carried out in two stages, first; the quantitative method by conducting surveys, second; the prototype method by making application products. The data in the first stage was taken through a questionnaire to 108 samples from 500 populations in several schools in Medan. The second stage was the creating of comic application product design by identifying problems, analyzing user needs, designing products according to user needs, making products that have been planned, and validating to the experts. The results of the first stage showed that 46% of respondents liked comics as a literacy medium, 12% did not like them, and 36% were neutral. Furthermore, the comic product design that had been made has received a very good assessment from the experts, but it needs to be tested on users first. There are many facilities that can be used as a medium for learning Islam, the availability of comic applications is one alternative that can be used especially for students in elementary schools.